Cognitive Behavioral Therapy: Recent Advances and Effectiveness - Sharma, Roopali (AG Volumes, 2025)
All throughout the world, people use cognitive behaviour therapy (CBT), an evidence-based treatment, with similar behavioural and cognitive integrity. A diverse array of emotional challenges and mental health conditions can be effectively addressed and managed through cognitive behavioural therapy. Throughout this article, we will examine a variety of literature that has investigated the efficacy and recent advancements of cognitive behavioural therapy. This review highlights that Cognitive Behavioral Therapy (CBT), including its third-wave approaches emphasizing mindfulness and acceptance, is effective in reducing psychological distress, anxiety, and depressive symptoms across diverse populations. Group-based CBT shows strong outcomes for anxiety reduction, while CBT-ED demonstrates promise for treating eating disorders, particularly in youth. The integration of digital and traditional CBT delivery models enhances accessibility and patient comfort but must ensure treatment fidelity. Though benefits are statistically significant, they often reflect modest effect sizes, emphasizing the need for individualized treatment dosing and sustained practice. Long-term efficacy and booster sessions warrant further investigation for lasting outcomes.